Competition, group identity, and social networks in the workplace: Evidence from a Chinese textile firm - Takao Kato; Pian Shu (Institute for the Study of Labor (IZA), 2011)
Using data on team assignment and weekly output for all weavers in an urban Chinese textile firm between April 2003 and March 2004, this paper studies a) how randomly assigned teammates affect an individual worker's behavior under a tournament-style incentive scheme, and b) how such effects interact with exogenously formed social networks in the manufacturing workplace. First, we find that a worker's performance improves when the average ability of her teammates increases. Second, we exploit the exogenous variations in workers' origins in the presence of the well-documented social divide between urban resident workers and rural migrant workers in large urban Chinese firms, and show that the coworker effects are only present if the teammates are of a different origin. In other words, workers do not act on pecuniary incentives to outperform teammates who are from the same social network. Our results point to the important role of group identities in overcoming self-interests and facilitating altruistic behavior.
urn:nbn:de:101:1-201201113910
Keywords: M5; J24; L2; 330; coworker effects in the workplace; social networks; intergroup competition; Arbeitsgruppe; Extensives Spiel; Arbeitsleistung; Soziale Gruppe; Soziales Netzwerk; Textilindustrie; China